Efficacy and feasibility of proton beam radiotherapy using the simultaneous integrated boost technique for locally advanced pancreatic cancer - Tae Hyun Kim (Nature Portfolio, 2020)
Abstract To evaluate the clinical efficacy and feasibility of proton beam radiotherapy (PBT) using the simultaneous integrated boost (SIB) technique in locally advanced pancreatic cancer (LAPC), 81 LAPC patients receiving PBT using SIB technique were analyzed. The prescribed doses to planning target volume (PTV)1 and PTV2 were 45 or 50 GyE and 30 GyE in 10 fractions, respectively. Of 81 patients, 18 patients received PBT without upfront and maintenance chemotherapy (group I), 44 received PBT followed by maintenance chemotherapy (group II), and 19 received PBT after upfront chemotherapy followed by maintenance chemotherapy (n = 16) (group III). The median follow-up time was 19.6 months (range 2.3–57.6 months), and the median overall survival (OS) times of all patients and of those in groups I, II, and III were 19.3 months (95% confidence interval [CI] 16.8–21.7 months), 15.3 months (95% CI 12.9–17.7 months), 18.3 months (95% CI 15.9–20.7 months), and 26.1 months (95% CI 17.8–34.3 months), respectively (p = 0.043). Acute and late grade ≥ 3 toxicities related to PBT were not observed. PBT with the SIB technique showed promising OS for LAPC patients with a safe toxicity profile, and intensive combinations of PBT and chemotherapy could improve OS in these patients.